2020
DOI: 10.1176/appi.ps.201800567
|View full text |Cite
|
Sign up to set email alerts
|

Serious Games, Gamification, and Serious Mental Illness: A Scoping Review

Abstract: The use of serious games and gamification to promote learning has a long history. More recently, serious games and gamification have been used in clinical settings to promote treatment and recovery. Yet there is little evidence to support their use with populations that experience serious mental illness.Methods: A scoping review was used to answer the following research question, What is the current state of knowledge about how games and gamification are used to promote treatment of serious mental illness? Sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(60 citation statements)
references
References 63 publications
1
50
0
9
Order By: Relevance
“…Therefore, authors have called for high-quality research on the efficacy of mental health apps as a stand-alone self-management option and an additional treatment option for mental health issues. Extending the theme of technology, some researchers and clinical practitioners noted the promise of video games tailored to assist with the treatment and management of a wide variety of clinical issues [51]. These games have been found to be successful in improving mental health outcomes in a variety of domains [51][52][53][54].…”
Section: Traditional Mental Health Care Versus Traditional Alternatives and Digital Technologymentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, authors have called for high-quality research on the efficacy of mental health apps as a stand-alone self-management option and an additional treatment option for mental health issues. Extending the theme of technology, some researchers and clinical practitioners noted the promise of video games tailored to assist with the treatment and management of a wide variety of clinical issues [51]. These games have been found to be successful in improving mental health outcomes in a variety of domains [51][52][53][54].…”
Section: Traditional Mental Health Care Versus Traditional Alternatives and Digital Technologymentioning
confidence: 99%
“…Extending the theme of technology, some researchers and clinical practitioners noted the promise of video games tailored to assist with the treatment and management of a wide variety of clinical issues [51]. These games have been found to be successful in improving mental health outcomes in a variety of domains [51][52][53][54]. Many bespoke video games (eg, the Pesky gNATs game) seem to be beneficial as alternatives to traditional treatments [55,56].…”
Section: Traditional Mental Health Care Versus Traditional Alternatives and Digital Technologymentioning
confidence: 99%
“…Games that are well designed and that integrate the game's technology adequately have higher levels of usability and acceptability by end users; thus, they are more successful in engaging users in game content and in achieving better outcomes. 69…”
Section: Rq7: What Is the Effectiveness Of Sgs In Dentistry?mentioning
confidence: 99%
“…It is suggested that digital intervention in the form of serious games may have a positive impact for young people internalising symptoms of mental health (57). Augmented and virtual reality adapted games have been used and found to be helpful for health care design and delivery, in physical and mental health conditions (58). Similarly, digital story telling has been implemented as a narrative intervention when working with survivors of trauma (59).…”
Section: How Effective Are Digital Intervention In Supporting Young People Exposed To Aces?mentioning
confidence: 99%